Kant and Hegel on Freedom - Göksel, Gülay Uğur (My University, 2021)
The main objective of this article is to understand Hegelian understanding of freedom through a comparison ofits Kantian counterpart. I set up this investigation with a consideration of the debate between liberals andcommunitarians. In the history of political thought, many political thinkers have been occupied by thequestions about the priority of right over good and of universal over particular. In order to answer thesequestions, one needs to have a clear conception of freedom since the claims of freedom and equality areuniversally accepted political values which should reflect our political institutions contextually. To accomplishthis task, first, I will introduce a brief account of Kant’s idea of freedom. It is crucial to know Kantian idea offreedom and how this idea reflects to his political philosophy to understand Hegel’s emphasis on ethical orderand particularly state institutions. Second, I will give a brief account of Hegel’s idea of freedom by givingreferences to his book titled Philosophy of Right. Third, I will introduce two major criticisms that Hegel posesto the Kantian idea of freedom. Finally, I will introduce how Hegel tries to overcome the problems of Kantianidea of freedom through the dialectical construction of the concepts of spirit, freedom and ethnical order.